AMERTHA SANJIWANI - Ni Putu Ayu Aneska Rastini Dewi; I Kt. Suteja; Ni Wayan Suartini (Jurnal IGEL : Journal Of Dance, 2021)
Purana Pura Luhur Tirta Mas Manik Muncar tells the story of the sacrifice of Ida Ratu Ayu Mas Membah who is willing to change her form from beautiful to old grandmother. The meaning of this story is symbolic of water which has an important role in human life. The phenomenon of this story is very unique and aesthetically raised into a creative dance work, because in the story water flows from upstream to downstream or from clean to dirty things. Departing from this, then created a dance work entitled Amertha Sanjiwani. The process of creating Amertha Sanjiwani's dance works, using the creation method of Creating Through Dance by Y. Sumandiyo Hadi, includes assessment, experimentation and formation. To clarify the results of this creation, transformation theory is used, namely transferring the essence of the Puranas story into a dance work, as well as interpreting the values contained in the story. Amertha Sanjiwani's dance work is a creative dance work that interprets the philosophy of holy water of faith-affirming life, and is implemented in the form of a goddess' sacrifice by changing her form from a beautiful goddess to an old grandmother in order to carry out a good mission.Keywords: Amertha Sanjiwani, water, sacrifice